Kontribusi Perilaku Kepemimpinan Kepala Sekolah dan Kinerja Mengajar Guru Terhadap Mutu Proses Pembelajaran Di SMK Kota Cirebon - eliyah eliyah (Exchall: Economic Challenge, 2021)
The focus of the problem in this study is how the contribution of the principal's leadership behavior and teacher teaching performance to the quality of the learning process in vocational high schools in Cirebon. This study aims to: (1). Know the real picture of the principal's leadership behavior towards the quality of the learning process at SMK Cirebon; (2). Knowing the real picture of the performance of teaching teachers to the quality of the learningprocess; (3). Knowing the magnitude of the contribution of the headmaster's leadership behavior and the performance of teaching teachers to the quality of the learning process at SMK Cirebon. The method used in this study is descriptive analysis with quantitative approach, the research population is vocational school in Cirebon with the number of 17 vocational schools and the number of teachers as many as 609 respondents and sampled proportionally as many as 86 respondents. The data was netted through instruments in the form of research questionnaires distributed to 86 teachers in 17 vocational schools in Cirebon. The results of the study obtained that, (1). The principal's leadership behavior was correlated by 0.537 or 53.7% and contributed with a coefficient of determination of 0.288 or 28.8%, (2). Teacher teaching performance was correlated by 0.372 or 37.2% and contributed with a coefficient of determination of 0.138 or 13.8%, (3). The principal's leadership behavior and teacher teaching performance had a correlation of 0.291 or 29.1% and the remaining 70.9% was influenced by other factors not studied in this study, such as policy, organizational climate, innovation, monitoring, reward and punishment, curriculum, facilities and infrastructure and so on. The recommendations given are (1). The ideas and feelings of subordinates related to the development of the school must be respected, the desire of subordinates to be able to continue to a higher school should be supported and the assignment should be done equally, so that the school can develop optimally, (2). The allocation of time at the time of practice, carrying out learning evaluations and conducting class action research should be conducted regularly, (3). Recommendations for further researchers, if conducted research on the quality of the learning process should be reviewed from other variables outside of this study as mentioned above. Keyword : Leadership behavior, performance, process quality